2015
DOI: 10.1177/0883073815592224
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Video Electroencephalographic (EEG) Monitoring for Electrographic Seizure Diagnosis in Neonates: A Single-Center Study

Abstract: The objective of this study was to determine the diagnostic yield of continuous video-electroencephalography (cEEG) monitoring in critically ill neonates in the setting of a novel, university-based Neonatal Neurocritical Care Service. Patient demographic characteristics, indication for seizure monitoring, and presence of electrographic seizures were obtained by chart review. Among 595 patients cared for by the Neonatal Neurocritical Care Service, 400 (67%) received cEEG. The median duration of cEEG monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 26 publications
0
27
2
Order By: Relevance
“…6 We note that patients monitored for ANE at our site had a slightly lower incidence of seizure compared to prior studies, which have reported seizures in 30%-65% of children with ANE. The study is limited in its scope as a single-center study and observational study design.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…6 We note that patients monitored for ANE at our site had a slightly lower incidence of seizure compared to prior studies, which have reported seizures in 30%-65% of children with ANE. The study is limited in its scope as a single-center study and observational study design.…”
Section: Discussioncontrasting
confidence: 49%
“…[1][2][3][4] Due to developing neurophysiology and immature movements, neonates are at high risk of subclinical seizures and misidentified seizures, 5,6 necessitating the use of continuous electroencephalography (cEEG) monitoring to accurately diagnose seizures. [1][2][3][4] Due to developing neurophysiology and immature movements, neonates are at high risk of subclinical seizures and misidentified seizures, 5,6 necessitating the use of continuous electroencephalography (cEEG) monitoring to accurately diagnose seizures.…”
Section: Introductionmentioning
confidence: 99%
“…Data from these 7 centers following ACNS guidelines add to the literature that supports the ACNS recommendations to monitor at-risk neonates with conventional video-EEG for at least 24 hours of continuous monitoring to identify subclinical seizures and confirm electrographic correlates of paroxysmal events 9,14 . High frequency of subclinical seizures has been reported in several previous studies of neonates, 3,15,16 and our much larger study population supports and extends this finding.…”
Section: Discussionmentioning
confidence: 92%
“…Given the absence of an occipital lesion or abnormal findings on dilated funduscopic exam, such a finding is unlikely to be related to a visual field deficit. Continuous video scalp EEG is frequently used in newborn infants, has a high sensitivity, is the gold standard for seizure monitoring in this age group [7,8,9,10] and is significantly more accurate than clinical detection [8]. Although the reported incidence of localized EEG ictal onset is somewhat low for frontal-lobe epilepsy [11], this is in part due to the fact that medial temporal lobe foci are relatively inaccessible to scalp EEG, while dorsolateral foci including the frontal eye fields are detected more frequently by scalp EEG [12].…”
Section: Discussionmentioning
confidence: 99%